2007
DOI: 10.1242/jcs.008664
|View full text |Cite
|
Sign up to set email alerts
|

Show and tell: visualizing gene expression in living cells

Abstract: The development of non-invasive methods of visualizing proteins and nucleic acids in living cells has provided profound insight into how they move and interact with each other in vivo. It is possible to evaluate basic mechanisms of gene expression, and to define their temporal and spatial parameters by using this methodology to label endogenous genes and make reporter constructs that allow specific DNA and RNA regulatory elements to be localized. This Commentary highlights recent reports that have used these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 72 publications
0
26
0
Order By: Relevance
“…Since many of these factors were discovered using techniques, which disrupt cellular architecture and average effects in cell populations, it is not known how or when critical regulators are selectively recruited to specific genomic sites in intact cells. One of the pivotal advances to imaging chromatin in single cells has been the development of reporter plasmids carrying sequence elements from bacteria and bacteriophage that allow DNA and RNA to be visualized in living cells (Rafalska-Metcalf and Janicki, 2007). The genomic sites into which these plasmids integrate can be visualized when their binding proteins, fused to auto-fluorescent proteins are expressed.…”
Section: Introductionmentioning
confidence: 99%
“…Since many of these factors were discovered using techniques, which disrupt cellular architecture and average effects in cell populations, it is not known how or when critical regulators are selectively recruited to specific genomic sites in intact cells. One of the pivotal advances to imaging chromatin in single cells has been the development of reporter plasmids carrying sequence elements from bacteria and bacteriophage that allow DNA and RNA to be visualized in living cells (Rafalska-Metcalf and Janicki, 2007). The genomic sites into which these plasmids integrate can be visualized when their binding proteins, fused to auto-fluorescent proteins are expressed.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have revealed widespread pausing and abortion by engaged Pol II (5)(6)(7)(8)(9)(10). Pol II dynamics have also been studied using fluorescence imaging (11)(12)(13)(14)(15), but it remains difficult to observe both the rapid recycling of Pol II (14) and the unstable nascent transcripts.…”
mentioning
confidence: 99%
“…However, multi-copy arrays of transgenes containing sequence elements that allow nuclei acids to be visualized in vivo can be easily localized (Rafalska-Metcalf and Janicki, 2007; Yunger et al, 2013a). When RNA pol II transcription units are included in these transgenes, transcriptional dynamics can be directly visualized at these arrays.…”
Section: Presentationmentioning
confidence: 99%